2013
DOI: 10.1371/journal.pone.0055038
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Microbial Translocation Markers in Patients on Efavirenz or Lopinavir/r Based Antiretroviral Therapy

Abstract: ObjectivesWe investigated whether there are differences in the effects on microbial translocation (MT) and enterocyte damage by different antiretroviral therapy (ART) regimens after 1.5 years and whether antibiotic use has impact on MT. In a randomized clinical trial (NCT01445223) on first line ART, patients started either lopinavir/r (LPV/r) (n = 34) or efavirenz (EFV) containing ART (n = 37). Lipopolysaccharide (LPS), sCD14, anti-flagellin antibodies and intestinal fatty acid binding protein (I-FABP) levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 45 publications
3
27
1
Order By: Relevance
“…Other studies have determined the effect of cART on microbial translocation markers such as I-FABP and sCD14, and similarly found I-FABP levels increased in individuals taking efavirenz (EFV) [38]. In our study, there was no correlation between I-FABP levels and treatment with EFV, and there was no bias of EFV usage in females over males.…”
Section: Discussionsupporting
confidence: 63%
“…Other studies have determined the effect of cART on microbial translocation markers such as I-FABP and sCD14, and similarly found I-FABP levels increased in individuals taking efavirenz (EFV) [38]. In our study, there was no correlation between I-FABP levels and treatment with EFV, and there was no bias of EFV usage in females over males.…”
Section: Discussionsupporting
confidence: 63%
“…A strong inverse correlation of sCD14 with CD4 + T cells and a direct correlation of sCD14 with VL have been previously reported. 5,46 We found an inverse correlation of sCD14 with CD4% but did not find any correlation with VL (data not shown). T-cell IA was correlated with monocyte activation at baseline, suggesting that there is generalized IA.…”
Section: Discussionmentioning
confidence: 68%
“…Although previous associations have been described between viral load and sCD14 levels [24], to our knowledge this is the first study to link baseline sCD14 with virologic response during ART. Although limited by the number of participants providing gut biopsies, we also observed that starting ART in early HIV infection did not improve recovery of CD4 + T-cell proportions in GALT, despite all participants starting ART within 30 days of EDI.…”
Section: Discussionmentioning
confidence: 92%
“…We also observed a significant and continued loss of central memory CD4 + T cells over time in the GALT despite ART. This could possibly be due to ongoing HIV replication in GALT, as previously described [26] or due to cell-mediated death of latently infected CD4 + T cells, especially in the presence of significantly increasing proportions of effector CD8 + T cells [2427,32,33]. …”
Section: Discussionmentioning
confidence: 93%